Analisis Faktor-Faktor Pengaruh Customer Loyalty dengan Customer Satisfaction sebagai Variabel Mediasi pada Pelanggan E-Commerce Batam - Tyana, Tyana; Qadri, Rizni Aulia; Sinambela, Fitriana Aidnilla (Universitas Hamzanwadi, 2024)
The development of the digital era supports the rapid growth of e-commerce businesses in Indonesia. E-commerce provides opportunities for seller to sell their products to targeted customers in a more effective way. This research aims to analyze the factors that could indfluence customer loyalty by mediating customer satisfaction. Analysis results can be use as indicators for consideration or reference for academic parties and business owner. The research conducted on Batam City e-commerce customers with a total sample of 401 respondents. The data was processed with Smart PLS using non-probability sampling techniques in research. The research results show that the relationship between product quality, service quality, advertising, public relations, and social media marketing has impact towards customer loyalty. From the results mentioned above, the more superior the factor will have an impact on customer loyalty which can provide long-term benefits to the business. The relationship between customer satisfaction and loyalty obtained insignificant results because it did not meet the criteria. The research shows that the results of the indirect relationship did not obtain significant results. Based on the results, it shows that if e-commerce entrepreneurs want to gain customer loyalty which can have a positive impact on their business in the long term, they need to improve certain factors